2004
DOI: 10.1038/sj.bmt.1704762
|View full text |Cite
|
Sign up to set email alerts
|

Side population/ABCG2-positive cells represent a heterogeneous group of haemopoietic cells: implications for the use of adult stem cells in transplantation and plasticity protocols

Abstract: Summary:Murine side population (SP) cells may have an increased ability to engraft lethally irradiated mice and lack CD34 expression. Strategies using CD34 as a primary marker of haemopoietic stem cells may therefore result in the exclusion of a primitive stem cell population. The molecular basis for the murine SP phenotype has been attributed to the multidrug-resistance transporter ABCG2. This study aimed to investigate ABCG2 expression from a variety of human sources and investigate the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…When the Hoechst 33342 efflux function was applied to Lin À cells, alone or in association with ALDH activity, the proportion of SP cells exceeded 2%-5% of Lin À cells. With regard to the proportion of Lin À cells in MNCs (about 1%-2%), this proportion was comparable with that described by others [33]. Similarly, the percentage of ALDH Br cells was not significantly different when the ALDEFLUOR technique was applied to Lin À cells alone or in combination with Hoechst staining (8.20% AE 3.19% versus 9.80% AE 6.34%, respectively).…”
Section: Discussionsupporting
confidence: 70%
“…When the Hoechst 33342 efflux function was applied to Lin À cells, alone or in association with ALDH activity, the proportion of SP cells exceeded 2%-5% of Lin À cells. With regard to the proportion of Lin À cells in MNCs (about 1%-2%), this proportion was comparable with that described by others [33]. Similarly, the percentage of ALDH Br cells was not significantly different when the ALDEFLUOR technique was applied to Lin À cells alone or in combination with Hoechst staining (8.20% AE 3.19% versus 9.80% AE 6.34%, respectively).…”
Section: Discussionsupporting
confidence: 70%
“…In addition to its role in drug disposition, ABCG2 has become a popular marker for identifying progenitor cells in a wide array of tissues, although its function in these cells is unclear (31)(32)(33)(34)(35). As an ABC superfamily member, ABCG2 is similar to other MRPs in its ability to protect cells against chemical insults; but it is unlike other MRPs in that ABCG2 is a member of the half-transporter G (WHITE) subfamily.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different research teams have demonstrated that ABCA3 and ABCG2 were expressed at higher levels in SP cells than in non-SP cells in human, rhesus monkey and mouse hematopoietic tissues; and microarray analysis indicated that several genes related to stem cells were substantially upregulated in the SP cells in comparison to non-SP cells [130,151,152]. This SP phenotype is present in several kinds of stem cells from different tissues, including the hematopoietic, meschenchymal, heart, liver, and pancreatic stem cells; it disappears with verapamil treatment thus indicating that the SP phenotype might result from the expression of ABC transporters in a primitive subset of stem cells in mammals [140,142,131,145,146,148,153,154]. Since SP stem cells show high repopulating activity and ABCA3, ABCB1 and ABCG2 expression, it has been hypothesized that the special phenotype of SP cells might be controlled or regulated by the expression of ABC transporters [142,144,145,149,155,156].…”
Section: Abc Transporters and Stem Cellsmentioning
confidence: 99%
“…In particular, ABCB1 is expressed in human CD34+ stem cells, which can be identified by their ability to transport fluorescent dyes like Rh123 and Hoechst-33342 [128,129,[137][138][139][140][141][142][143]. Interestingly, the SP phenotype in rodent and human tissues often appears to be specifically determined by the expression of an ABC transporter: for example, both ABCB1 and ABCG2 transporters are highly expressed in the SP of stem cells from different tissues such as brain, bone marrow, pancreas, liver and others, all of which can be isolated based on the cells' ability to promote the efflux of the Hoechst-33342 fluorescent dye [9,[129][130][131][132][133][134][135][136][142][143][144][145][146][147][148][149][150]. Moreover, different research teams have demonstrated that ABCA3 and ABCG2 were expressed at higher levels in SP cells than in non-SP cells in human, rhesus monkey and mouse hematopoietic tissues; and microarray analysis indicated that several genes related to stem cells were substantially upregulated in the SP cells in comparison to non-SP cells [130,151,152].…”
Section: Abc Transporters and Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation